Theoretical Foundations of Economic Growth of Livestock Producers - Chub, O.; Kalchenko, M. (Економічний вісник Донбасу, 2025)
The article is devoted to the study of the theoretical foundations of the economic growth of livestock producers. The study is key to the formation of effective agricultural policy, the development of sustainable business models and ensuring the long-term viability and competitiveness of the industry, which ultimately affects the well-being of society. It is determined that the economic growth of livestock producers depends on the complex interaction of internal factors (production, personnel, management, innovation potential) and external influences (market conditions, state policy, natural and climatic and socio-economic factors). Success is achieved when the enterprise can effectively use its internal capabilities, adapting to external challenges. It is established that the development and effective use of production capacity, human capital, market position and management potential are the foundation of economic growth. Each of these elements is interconnected: qualified personnel (human capital) use production facilities more efficiently, competent management (management potential) allows for better adaptation to market conditions and the introduction of innovations. The need to consider the unique features of the industry (biological nature of production, duration of the production cycle, high capital intensity, dependence on the feed base and veterinary and sanitary requirements) has been proven. These factors dictate special approaches to planning, management and investment. It has been substantiated that to ensure sustainable and effective economic growth of livestock producers, not only a sound theoretical basis based on market economic laws is required, but also the practical implementation of strategies that combine intensification, innovation and the principles of sustainable development. This will allow the industry not only to increase volumes, but also to produce high-quality, competitive products, minimizing risks and ensuring long-term development prospects. Стаття присвячена дослідженню теоретичних основ економічного зростання виробників продукції тваринництва. Дослідження є ключовим для формування ефективної аграрної політики, розробки стійких бізнес-моделей та забезпечення довгострокової життєздатності та конкурентоспроможності галузі, що в кінцевому підсумку впливає на добробут суспільства в цілому. Визначено, що економічне зростання виробників продукції тваринництва залежить від складної взаємодії внутрішніх факторів (виробничий, кадровий, управлінський, інноваційний потенціали) та зовнішніх впливів (ринкові умови, державна політика, природно-кліматичні та соціально-економічні чинники). Успіх досягається тоді, коли підприємство вміє ефективно використовувати свої внутрішні можливості, адаптуючись до зовнішніх викликів. Встановлено, що розвиток та ефективне використання виробничої потужності, людського капіталу, ринкової позиції та управлінського потенціалу є фундаментом економічного зростання. Кожен із цих елементів взаємопов'язаний: кваліфікований персонал (людський капітал) ефективніше використовує виробничі потужності, грамотне управління (управлінський потенціал) дозволяє краще адаптуватися до ринкових умов та впроваджувати інновації. Доведена необхідність врахування унікальної особливості галузі (біологічний характер виробництва, тривалість виробничого циклу, висока фондомісткість, залежність від кормової бази та ветеринарно-санітарних вимог). Ці фактори диктують особливі підходи до планування, управління та інвестицій. Обґрунтовано, що для забезпечення сталого та ефективного економічного зростання виробників продукції тваринництва потрібна не лише обґрунтована теоретична база, яка спирається на ринкові економічні закони, а й практична реалізація стратегій, що поєднують інтенсифікацію, інновації та принципи сталого розвитку. Це дозволить галузі не тільки нарощувати обсяги, а й виробляти якісну, конкурентоспроможну продукцію, мінімізуючи ризики та забезпечуючи довгострокову перспективу розвитку.